An understanding of the motivations that influence the beef cattle production systems adopted by farmers in central Mozambique - Télis Adolfo Cumbe; Benedito Armando Cunguara; Concepta Margaret McManus; Antónia Mendes Paizano Alforma; Júlio Otávio Jardim Barcellos (PLoS ONE, 2025)
The analysis of factors that affect livestock production, from the farmers’ perspective, is essential for improving efficiency in animal production. The objectives of this study were to analyse: i) the historical and current motivations for beef cattle production and ii) the situation of communal pasture areas. For data collection, semi-structured interviews were held with one hundred and one farmers in the districts of Angónia, Changara and Manica, in Mozambique. The results show that in Angónia and Changara districts, the primary motivation for starting beef cattle production was to keep cattle as a saving asset, whereas the primary motivation of Manica’s farmers was to use cattle as draught animal power to expand crop production. These motivations remain the same over the years of the farmers’ experience. Grazing areas have decreased over the years, mainly due to their occupation for crop production, and this perception was associated with the studied district (p = 0.004). The studied districts, particularly Angónia and Manica, have similar characteristics, suggesting that similar intervention models may be designed. The results raise the question of how to increase the productivity of beef cattle systems, primarily motivated by savings and animal traction while maintaining their characteristics, which are essential for the socio-economic conditions of the farmers. Overall, the study suggests that motivations for beef cattle production and the establishment of grazing areas should be considered when developing strategies and policies to improve these systems.